H. T. Klami, The Legalists. Finnish legal science in the period of autonomy 1809-1917 - Kodrębski, Jan (Czasopismo Prawno-Historyczne, 1983)
Recenzja: Hannu Tapani Klami, The Legalists. Finnish legal science in the period of autonomy 1809-1917, Helsinki 1931, Societas Scientiarum Fennica